Penilaian Risiko Pekerjaan Produksi Suku Cadang Kendaraan Dengan Hazard Identification Risk Assessment (Studi Kasus PT. XYZ) - Indra Rizki Pratama; Lucyana Tresia; Dianasanti Salati; Kingwan Kingwan (Universitas Batanghari Jambi, 2023)
Industrial development in each sector positively impacts the economy, and this also correlates with higher work accidents. Work accidents show an increasing trend every year, and the value of payment claims increases, so an analysis of work activities is needed. One job with a high accident rate is manufacturing work, PT. XYZ is an industrial company that produces spare parts. Hazard Identification Risk Assessment (HIRA) is a method for identifying and assessing the risks of each work activity. The purpose of this research is to identify activities at PT. XYZ using the Hazard Identification Risk Assessment (HIRA) method, observations were made on one of the production lines at PT. XYZ. The results found that from 7 activities in the observed production line, 10 potential hazards occurred, were 5 activities had a high risk of hobbing gear kick machines, lathes, and welding machines. Then the other 5 activities have a moderate risk: hobbing machines, broaching & drilling machines, CNC machines, and final check tables. Minimize the occurrence of exposure done is by using hierarchy of control.